2017
DOI: 10.4067/s0717-95022017000401243
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Relationships of Mandibular Canal. A Cone Beam CT Study

Abstract: SUMMARY:It is critical to know the precise location and configuration of the mandibular canal (MC) to avoid damages in the alveolar inferior nerve during an invasive dental treatment. The aim of this study was to provide anatomic relationships of the mandibular canal in its entire pathway related to cortical walls and dental roots to serve as basic knowledge for dental clinical procedures performed in this area. We analyzed 50 CBCT images assessing the specific location of MC at the retromolar space as related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…Previous studies that used CBCT reconstructions employed different anatomical structures as the points of measurement, including bone margins, 15 the mental foramen, 16 or the root apices. 6 7 17 18 19 20 21 22 23 24 25 26 27 28 29 The relationship between the root apices and the bone margin or mental foramen is important for surgery, endodontic microsurgery, and implant procedures. Knowledge of the relationship between the root apices and the MC is important for endodontic treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that used CBCT reconstructions employed different anatomical structures as the points of measurement, including bone margins, 15 the mental foramen, 16 or the root apices. 6 7 17 18 19 20 21 22 23 24 25 26 27 28 29 The relationship between the root apices and the bone margin or mental foramen is important for surgery, endodontic microsurgery, and implant procedures. Knowledge of the relationship between the root apices and the MC is important for endodontic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the relationship between the root apices and the MC is important for endodontic treatments. When the root apices were used as a reference point, some studies reported the position of the MC in millimetres, 6 7 17 18 19 20 21 23 24 26 27 28 29 while another described the contact or lack of contact between the MC and the root tips 25 and yet others described the position of the MC relative to the roots (i.e., lingual; buccal; interradicular; lingual and interradicular; apical/inferior/in-line with the apex/middle; lingual and inferior; buccal and inferior; or interradicular and inferior). 22 Studies that used root apices as the reference points and made measurements in millimetres used different definitions of the reference point on the MC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muñoz y asociados, 21 en su investigación al evaluar la relación de los ápices de los segundos molares inferiores con el conducto dentario inferior, determinan que la distancia promedio de la raíz distal del lado derecho es de 4.3 mm y del lado izquierdo de 3.6 mm; la raíz mesial presenta una distancia media del lado derecho de 5.1 mm y del lado izquierdo de 4.6 mm.…”
Section: Edades (Años)unclassified
“…En Chile, existen dos estudios (Fuentes et al, 2017;Cartes et al, 2018), que utilizaron radiografías panorámicas para evaluar la posición del FM, sin embargo, la principal limitación de este método es la superposición de estructuras por ser una imagen bidimensional de una estructura tridimensional, además que la imagen resultante no muestra el detalle fino (White & Pharoah, 2002). En el año 2017, se publicó un estudio en una población chilena, en el cual se utilizaron 50 CBCT y relacionaron el canal mandibular con las corticales bucal, lingual y además con los ápices de los dientes mandibulares, encontrando que el FM se encontraba entre los premolares inferiores (Muñoz et al, 2017).…”
Section: Introductionunclassified